Management Of Personal Information By SMAN 1 Cicalengka Students In Overcoming Learning Obstacles During The Covid-19 Pandemic - Mindy Syailah Nurthoyyibah; Laksmi Dewi; Dian Arya Susanti (Universitas Airlangga, 2021)
The Covid-19 pandemic purpose challenges to all parties in various human activities, especially education. The implementation of distance learning is one of the right solutions for current teaching and learning activities. Information that continues to grow can be a help or even a loss because of the accumulation of information. The presence of distance learning and the rapid development of information at this time have an impact on students, one of which is learning obstacles. Learning barriers have a negative impact on the development of students' competence and knowledge. This study uses a descriptive quantitative method with rating scale analysis including the calculation of the minimum index value, maximum index value, interval, interval distance and percentage score, as well as data analysis assisted by IBM SPSS Statistics 25. Personal information management can be one solution to overcome problems that arise. users are facing. The results of the study revealed that students' personal information management activities were classified as good, but there was a need for improvement and more attention, especially the stages of storing, organizing, and maintaining for the success of the information retrieval process. Personal information management also has a positive relationship and influence on student learning constraints during the Covid-19 pandemic.